Mulligan mobilization versus traction in lumbar facet joint syndrome: randomized controlled trial - Mohammed Hussien Elgendy; Ahmed Abduallah Habib; Ramy Edward Ibrahim; Yasser Ramzy Lasheen (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.